MEMBANGUN PERADABAN KASIH DALAM MASYARAKAT MULTIKULTURAL DI ERA DISRUPSI - Paskalis Bruno Syukur (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2021)
This seminar challenges the contribution of the Catechetical Pastoral College. The swooping question is in what form does this educational institution participate in building human civilization? What patterned civilization was created by this educational institution. In other words, the relevance and meaning of the existence of a study program at this institution is questioned.